Sonja Stojanovic. Mind the Ghost. Thinking Memory and the Untimely through Contemporary Fiction in French. Liverpool UP, 2023. - Catherine Nesci (Studies in 20th & 21st Century Literature, 2024)
Review of Sonja Stojanovic. Mind the Ghost. Thinking Memory and the Untimely through Contemporary Fiction in French. Liverpool UP, 2023. xi + 307 pp.
Keywords: Memory; ghost; spectrality; contemporary French fiction